Apocalypses in context : apocalyptic currents through history - Murphy, Kelly J.; Schedtler, Justin Jeffcoat, 1977- (Minneapolis, Fortress Press, 2016)
Apocalyptic scenarios remain prevalent and powerful in popular culture (in television, film, comic books, and popular fiction), in politics (in debates on climate change, environmentalism, Middle East policy, and military planning), and in various religious traditions. Academic interest in apocalypticism is flourishing; indeed, the study of both ancient and contemporary apocalyptic phenomena has long been a focus of attention in scholarly research and a ready way to engage the religious studies classroom. Apocalypses in Context is designed for just such a classroom, bringing together the insights of scholars in various fields and using different methods to discuss the manifestations of apocalyptic enthusiasm in different ages (Part I: Ancient Apocalyptic Literature; Part II: Apocalypticism through the Ages; Part III: Apocalypticism in the Contemporary World). This approach enables the instructor to make connections and students to recognize continuities and contrasts across history. Apocalypses in Context features illustrations, graphs, study questions, and suggestions for further reading after each chapter, as well as recommended media and artwork to support the college classroom.
Part I. Apocalypticism in the ancient world. 1. Introduction--from before the Bible to beyond the Bible : apocalypses throughout history / Justin Jeffcoat Schedtler and Kelly J. Murphy -- 2. The first apocalypse (Daniel 7-12) : a story told backwards / Christopher B. Hays -- 3. "Proto-apocalyptic" constellations in the Bible and the ancient Near East : revelation, interpretation, combat, and judgment / Christopher B. Hays -- 4. Apocalyptic literature beyond the biblical canons : fallen angels, divine journeys, and the meaning of life / Jackie Wyse-Rhodes -- 5. Apocalyptic movements in early Judaism : dissonance and resistance / Robert Williamson Jr. and Justin Jeffcoat Schedtler -- 6. Apocalyptic currents in early Christianity : one-trick ponies? / Greg Carey -- 7. Paul--the apocalyptic apostle / Joshua W. Jipp -- 8. The beast or the lamb in the Apocalypse to John : will the real emperor please stand up? / Justin Jeffcoat Schedtler -- part II. Apocalypticism throughout the ages. 9. The transformation of the apocalyptic heritage in late antique Christianity / Karl Shuve -- 10. The decline of Second Temple Jewish apocalypticism and the rise of Rabbinic Judaism / Shayna Sheinfeld -- 11. The end of the world... again? : apocalypticism in medieval Christianity / Travis Ables -- 12. Apocalypse in Islam / Mohamed Mosaad Abdelaziz Mohamed -- 13. What kind of world is possible? : biblical apocalyptic literature and visual art / Brennan Breed -- part III. Apocalypticism in the contemporary world. 14. The last metamorphosis of labor : work, technology, and the end of the world / Michael J. Thate -- 15. What does modernity have to do with the New Jerusalem? : apocalypticism and modern European philosophy / Thomas Fabisiak -- 16. Revelatory film : apocalyptic themes in film and cinematic apocalypses / Matthew S. Rindge -- 17. The planet's apocalypse : the rhetoric of climate change / Ingrid Esther Lilly -- 18. Post-bankruptcy Detroit as apocalyptic sign of the times / James W. Perkinson -- 19. Apocalyptic America : buying the end time / Robert von Thaden Jr. -- 20. Space brothers and Mayan calendars : making sense of "doomsday cults" / Joseph P. Laycock -- 21. The end is (still) all around : the zombie and contemporary apocalyptic thought / Kelly J. Murphy.
Includes bibliographical references and index.
Keywords: Apocalyptic literature -- History and criticism; Apocalypse in motion pictures; PROTO-APOCALYPTIC